Analyzing the Effect of Technology-Based Intervention in Language Laboratory to Improve Listening Skills of First Year Engineering Students - Pasupathi, Madhumathi (PROFILE issues in teachers' professional development, 2013)
First year students pursuing engineering education face problems with their listening skills. Most of the Indian schools use a bilingual method for teaching subjects from primary school through high school. Nonetheless, students entering university education develop anxiety in listening to classroomlectures in English. This article reports an exploratory study that aimed to find out whether the listening competences of students improved when technology was deployed in language laboratory. It also investigated the opinions of the students about using teacher-suggested websites for acquiring listening skills. The results of the study indicated that the use of technology in a language laboratory for training students in listening competences had reduced the anxiety of the students when listening to English. Further, there was a significant improvement on the part of students in acquiring listening skills through technology-based intervention. Muchos estudiantes de ingeniería de primer año en India tienen problemas con sus habilidades de escucha en inglés; experimentan ansiedad al momento de escuchar conferencias en inglés, pese a que provienen de colegios donde se sigue un modelo bilingüe para enseñar materias desde la primariahasta la secundaria. Con el objetivo de averiguar si las competencias de escucha de los estudiantes mejoran cuando se introduce la tecnología en el laboratorio de idiomas, se realizó un estudio exploratorio en el que se tuvieron en cuenta las opiniones de los estudiantes acerca del uso de sitios web sugeridos por el docente para adquirir habilidades de escucha. Los resultados indican que el uso de la tecnología en el laboratorio de idiomas reduce la ansiedad de los estudiantes al momento de escuchar conferencias en inglés y que progresan significativamente en sus habilidades de escucha.